2019
DOI: 10.1002/pbc.27719
|View full text |Cite
|
Sign up to set email alerts
|

Capped antithrombin III dosing is cost effective in the management of asparaginase‐associated thrombosis

Abstract: Asparaginase therapy induces a transient antithrombin III (ATIII) deficiency, which contributes to the risk of asparaginase‐induced thrombosis. At Cincinnati Children's Hospital Medical Center, management of asparaginase‐induced thrombosis includes ATIII supplementation during therapeutic anticoagulation with enoxaparin. Due to the expense associated with ATIII, a capped dosing approach for ATIII was evaluated in this population. Peak ATIII levels were obtained following capped doses to evaluate response. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…A recent single‐center study of exogenous AT supplementation demonstrated reduced incidence of recurrent VTE, 4 and while efficacy is unclear, AT use in pediatrics is rising 13 . There is lack of uniformity about threshold for AT replacement, and <70% was adapted at our institution based on published cut‐off values for AT supplementation in anticoagulated ALL/L patients 4,12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent single‐center study of exogenous AT supplementation demonstrated reduced incidence of recurrent VTE, 4 and while efficacy is unclear, AT use in pediatrics is rising 13 . There is lack of uniformity about threshold for AT replacement, and <70% was adapted at our institution based on published cut‐off values for AT supplementation in anticoagulated ALL/L patients 4,12 …”
Section: Discussionmentioning
confidence: 99%
“…LMWH effect on coagulation factor Xa depends upon AT. Although the safety and efficacy of thromboprophylaxis with AT supplementation during induction chemotherapy continues to be evaluated, 7‐11 our institution has a protocol for supplementation of AT if <70% in anticoagulated ALL and lymphoma (ALL/L) patients with thrombosis who are receiving L‐asparaginase 4,12,13 . How much variable AT activity impacts the gold‐standard anti‐Xa assay for LMWH monitoring is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of AT therapy has been described as a barrier to its use, 145 but the patient benefits associated with AT therapy can offset upfront costs. 99,[145][146][147] The acquisition cost of ATc varies between and within institutions and according to other location-and time-sensitive economic factors.…”
Section: Current Costsmentioning
confidence: 99%
“…The cost of AT therapy has been described as a barrier to its use, 145 but the patient benefits associated with AT therapy can offset upfront costs. 99,[145][146][147] The acquisition cost of ATc varies between and within institutions and according to other location-and time-sensitive economic factors. 146 A 2018 costeffectiveness study from the Johns Hopkins Hospital estimated the acquisition cost of a 500U vial of ATc (Thrombate III) to be US$2330 or $4.66 per unit.…”
Section: Current Costsmentioning
confidence: 99%
See 1 more Smart Citation